Electron Storage Performance of Hybrid Materials Comprising Polyoxometalates and Carbon Nanohorns as Cathode‐Active Materials. Issue 1 (24th November 2022) - Wakamatsu, Katsuhiro; Sekihara, Akinori; Yamaguchi, Yoshihiko; Matsushima, Ryo; Matsumura, Daiju; Kuila, Tapas; Yoshikawa, Hirofumi
Abstract: Nanohybrid materials comprising polyoxometalates (POMs) and nanocarbons have attracted considerable attention as electrode‐active materials for rechargeable lithium‐ion batteries (LIBs). These materials exhibit multi‐electron redox reactions, resulting in an improved battery capacity. This study focuses on carbon nanohorns (CNHs) as a nanocarbon material and evaluates the battery performance using POM/CNH hybrids as cathode‐active materials. X‐ray absorption fine structural analysis was performed to investigate the reaction mechanism of these hybrids. POM/oxidized CNH (CNHox) hybrid materials maintain high capacities at high current densities as the high surface area availability of CNHox leads to high electrical double‐layer capacitances. These findings show an improved performance of the as‐developed material when compared with those reported in previous papers and can contribute toward an improved design of cathode‐active materials for high‐performance supercapacitors. Abstract : Nanohybrid materials for high‐performance LIB cathodes : Nanohybrid materials consisting of oxidized polyoxometalates and carbon nanohorns produced high capacity even at high current densities owing to synergistic effects of the super‐reduction of polyoxometalates and the increased electrical double layer capacitances due to nanohybridization with oxidized carbon nanohorns with large surface areas.